Control Algorithm for Equal Current Sharing between Parallel-Connected Boost Converters in a DC Microgrid - Muamer M. Shebani; M. Tariq Iqbal; John E. Quaicoe (Journal of Electrical and Computer Engineering)
DC microgrids are gaining more attention compared to AC microgrids due to their high efficiency and uncomplicated interconnection of renewable sources. In standalone DC microgrid, parallel-connected converters connect the storage system to the load. To achieve equal current sharing among parallel converters, several methods have been presented, but they vary in their current sharing performance, complexity, cost, and reliability. In DC microgrid, the conventional droop control method is preferred because it is more competitive in terms of cost, suitability, and reliability compared to the master-slave control method. However, the conventional droop method cannot ensure equal current sharing due to the mismatches in parameters of parallel-connected converters. To address this limitation, a control algorithm that supervises a modified droop method to achieve precise current sharing between parallel modules is proposed in this paper. The control algorithm is based on the percentage of current sharing for each module to the total load current. The output current measurement of each converter is compared to the total load current and is used to modify the nominal voltage for each converter. The effectiveness of the proposed algorithm is verified by MATLAB simulation model and experimental results.